Central hemodynamic response rates and baroreflectory sensitivity of vascular resistance rates in athletes taking caffeine at rest - Tambovtseva, R. V.; Orel, V. R.; Zhumaev, O. V. (Theory and Practice of Physical Culture, 2017)
Objective of the study was to profile the haemodynamic response rates in the athletes taking varying doses of caffeine in recovery periods following physical loads. Subject to the experiment were 23 highly skilled athletes from different sport disciplines. The study data archived in REODIN-504 System included HR data, stroke volume, heart cycle phases and blood pressure. These input data were applied to compute the elastic (Ea) and peripheral (R) resistance of the arterial system. The study data and analyses showed statistically significant changes 20-30 minutes after the caffeine intake including the following: significant HR reduction; significant growth of the stroke volume (SV); and significant reduction of the baroreflectory sensitivity for the peripheral versus elastic resistance rates of the arterial system.